Peran Komunikasi Pemasaran dalam Loyalitas Konsumen terhadap Produk Lokal ”Pusat Buah” di Era Digital - Muhammad Iqbal Fathoni; Sahri Aflah Ramadiansyah (Badan Penerbit STIEPARI Press, 2026)
This study examines the role of marketing communication in shaping consumer loyalty toward the local product “Pusat Buah” in the digital era. The research focuses on how marketing communication strategies implemented by business actors create emotional attachment and consumer trust toward local products amidst increasingly open digital market competition. This study employs a descriptive qualitative approach using interviews and observations with both consumers and the management of “Pusat Buah.” The findings reveal that consistent, informative, and interactive marketing communication through digital media plays an essential role in strengthening brand image and building long-term relationships with consumers. Furthermore, messages delivered through digital platforms such as social media and instant messaging applications serve as effective tools for maintaining consumer loyalty to local products. These findings confirm that marketing communication functions not only as a promotional tool but also as a strategic form of interaction that sustains consumer trust and commitment toward local brands in the digital era.